2022
DOI: 10.5604/01.3001.0016.2166
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrasound (QUS) of bone in sport

Abstract: Background. The quantitative examination of bone tissue is primarily associated with the diagnosis of osteoporosis. Osteoporosis is rarely suspected among athletes, usually young, active, and generally healthy. Quantitative research of bone tissue related to the sport has a preventive dimension. Increasing the parameters of bone tissue strength, especially reaching the maximum value of peak bone strength in childhood, adolescence, and early adulthood due to practicing sports can contribute to maintaining bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Papers have rarely focused on middle-aged groups. Several reviews have shown that various martial arts exercises can improve bone quality, balance, and falls risk in adults and older adults [43,44,48,125,126]. Gravitational exercises play a crucial role in martial arts performance.…”
Section: Skeletal Status Assessed With Qus and Pa And Non-combat Sportsmentioning
confidence: 99%
“…Papers have rarely focused on middle-aged groups. Several reviews have shown that various martial arts exercises can improve bone quality, balance, and falls risk in adults and older adults [43,44,48,125,126]. Gravitational exercises play a crucial role in martial arts performance.…”
Section: Skeletal Status Assessed With Qus and Pa And Non-combat Sportsmentioning
confidence: 99%